STUDIES IN MARINE GEOPHYSICS AND UNDERWATER SOUND FROM DRIFTING ICE STATIONS - Hunkins, Kenneth (1968)
Contents: Operations at Fletcher's ice island (T-3) and work at Lamont; Bathymetry; Gravity; Magnetics; Seismic profiler; Hydrographic work; Ocean temperature; Tiltmeter; Seismic investigations; Scattering layers; Ocean currents; Long-range sound propagation; Marine geophysical data analysis; Navigation.